Assessing new dimensions of attentional functions in children prenatally exposed to environmental contaminants using an adapted Posner paradigm - Éthier, Audrey-Anne; Ayotte, Pierre; Muckle, Gina; Jacobson, Sandra W.; Jacobson, Joseph L.; Saint-Amour, Dave (Neurotoxicology and Teratology, 2016)
Chronic exposure to methylmercury (MeHg), lead (Pb) and polychlorinated biphenyls (PCBs) has been associated with a range of attention deficits in children, but it is not known whether selective spatial attention is also altered. We modified the classic Posner paradigm, which assesses visuospatial attention, to also assess vigilance and impulsivity. This paradigm is based on the well-documented findings that a target will be detected more quickly if a visual cue indicates beforehand where it will appear, and more slowly if the cue indicates a false spatial location. In our task, visual distractors were introduced, in addition to the classic Posner trials, to assess impulsivity, and a central smiley face, whose eye-movement cued the location of the targets, to measure spatial attention. This task was administered to 27 school-age Inuit children (mean age = 11.2 years) from Nunavik (Arctic Quebec, Canada), in which pre- and postnatal exposures to environmental contaminants had been documented from birth. After controlling for the impact of confounding variables, multivariable regressions revealed that prenatal exposures to PCBs and Pb were significantly associated with greater inattention and impulsivity, respectively, while current exposure to Pb was significantly associated with longer reaction times. Although a significant correlation was observed between cord blood PCB concentration and decreased visuospatial performance, no significant association was found after adjustment for confounders. No effect was found for Hg exposures. These results suggest that our adapted Posner paradigm is sensitive in detecting a range of attention deficits in children exposed to environmental contaminants; implications for future studies are discussed.